Advanced composites in bridge construction and repair - Kim, Yail J., 1971- (Woodhead Publishing series in civil and structural engineering, 2014)
Advanced composite materials for bridge structures are recognized as a promising alternative to conventional construction materials such as steel. This book summarises key recent research in this area. After an introductory overview and an assessment of bond characteristics between composites and cement, Advanced composites in bridge construction and repair reviews key applications of fiber-reinforced polymer (FRP) composites in bridge construction and repair. These applications include cable-stayed bridges, seismic retrofit of reinforced concrete piers, repair of ageing bridge substructures a.